Drainage Pathway of the Superior Petrosal Vein Evaluated by CT Venography in Petroclival Meningioma Surgery - Kaku, Shougo; Miyahara, Kosuke; Fujitsu, Kazuhiko; Hataoka, Shunsuke; Tanino, Shin; Okada, Tomu; Ichikawa, Teruo; Abe, Toshiaki (Journal of Neurological Surgery Part B: Skull Base, 2012)
Objectives This study aimed to clarify the drainage location of the superior petrosal vein (SPV) in relation to Meckel's cave and the internal acoustic meatus (IAM) and to discuss its significance in petroclival meningioma surgery.Design Prospective clinical study.Setting Hospital-based.Participants Five patients with petroclival meningioma and 50 patients (primarily unruptured supratentorial aneurysm patients, with a few hemifacial spasm patients) with no posterior fossa lesions.Main Outcome Measures On computed tomography venography (CTV), the drainage site was classified into three patterns based on its relationship to Meckel's cave and the IAM: Meckel's cave type, Intermediate type, and Meatal type.Results In all patients, the SPV was patent and emptied into the superior petrosal sinus (SPS). In patients without posterior fossa lesions, 35% had Meckel's cave type, 54% had Intermediate type, and 11% had Meatal type. Of the five patients with petroclival meningioma, three had Intermediate type, and two had Meckel's cave type.Conclusion The SPV is a significant vein that should be preserved to prevent venous complications. Preoperative knowledge of the SPV drainage site is helpful for planning the approach and preserving the SPV in petroclival meningioma surgery.
Keywords: petrosal vein; computed tomography venography; petroclival meningioma; transpetrosal approach